Personal, indoor, and outdoor exposure to VOCs in the immediate vicinity of a local airport - Jung, Kyung-Hwa; Artigas, Francisco; Shin, Jin Young (Environmental monitoring and assessment, 2011)
This study measures the effect of emissions from an airport on the air quality of surrounding neighborhoods. The ambient concentrations of benzene, toluene, ethylbenzene, and o-, m-, and p-xylene (BTEX) were measured using passive samplers at 15 households located close to the airport (indoor, outdoor, and personal), at the end of airport runways and an out-of-neighborhood location. Measurements occurred over a 48-h period during summer 2006 and winter 2006-2007. The average concentrations were 0.84, 3.21, 0.30, 0.99, and 0.34 μg/m³ at the airport runways and 0.84, 3.76, 0.39, 1.22, and 0.39 μg/m³ in the neighborhood for benzene, toluene, ethylbenzene, m-, p-, and o-xylene. The average neighborhood concentrations were not significantly different to those measured at the airport runways and were higher than the out-of-neighborhood location (0.48, 1.09, 0.15, 0.78, and 0.43 μg/m³, each BTEX). B/T ratios were used as a tracer for emission sources and the average B/T ratio at the airport and outdoors were 0.20 and 0.23 for the summer and 0.40 and 0.42 for the winter, suggesting that both areas are affected by the same emission source. Personal exposure was closely related to levels in the indoor environment where subjects spent most of their time. Indoor/outdoor (I/O) ratios for BTEX ranged from 1.13 to 2.60 and 1.41 to 3.02 for summer and winter. The seasonal differences in I/O ratios reflected residential ventilation patterns, resulting in increased indoor concentrations of volatile organic compounds during winter.